2018
DOI: 10.1016/j.jmsy.2018.02.004
|View full text |Cite
|
Sign up to set email alerts
|

A survey of the advancing use and development of machine learning in smart manufacturing

Abstract: Machine learning (ML) (a subset of artificial intelligence that focuses on autonomous computer knowledge gain) is actively being used across many domains, such as entertainment, commerce, and increasingly in industrial settings. The wide applicability and low barriers for development of these algorithms are allowing for innovations, once thought unattainable, to be realized in an ever more digital world. As these innovations continue across industries, the manufacturing industry has also begun to gain benefits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
69
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(89 citation statements)
references
References 34 publications
0
69
0
2
Order By: Relevance
“…Machine learning continues to gain traction and interest as a useful tool in the generation of knowledge from data [32,33], particularly within the field of manufacturing [34]; as the use of machine learning techniques enables complex, non-linear and temporal relationships to be modelled easily through the use of historical data reserves. Neural networks have been successfully implemented in a number of applications and provide a nondeterministic method of matching a number of input variables to an output, and for approximating relationships between multidimensional data.…”
Section: ) Machine Learningmentioning
confidence: 99%
“…Machine learning continues to gain traction and interest as a useful tool in the generation of knowledge from data [32,33], particularly within the field of manufacturing [34]; as the use of machine learning techniques enables complex, non-linear and temporal relationships to be modelled easily through the use of historical data reserves. Neural networks have been successfully implemented in a number of applications and provide a nondeterministic method of matching a number of input variables to an output, and for approximating relationships between multidimensional data.…”
Section: ) Machine Learningmentioning
confidence: 99%
“…Work has shown that data-driven methods can, from build data, model how process parameters affect the quality of final parts [28][29] [30]. Approaches that utilise build data are advantageous because they provide great opportunities for digitalisation and smart process control, otherwise known as 'smart manufacturing' [31][32] [33].…”
Section: Machine Learning Approachesmentioning
confidence: 99%
“…In the manufacturing field, Industry 4.0 is characterized by the autonomous systems with cyber and physical representation [20][21][22] and advance in ICT [23] such as cloud computing [24], internet of things (IoT), internet of service (IoS) [25][26][27][28][29], agent technology [30][31][32][33][34][35], cognitive technology [36,37], big data [38,39], data mining [40,41], and artificial intelligence [42][43][44][45][46][47]. Smart manufacturing systems (SMS) built with intelligent cyber-physical systems (CPSs) are the heart of the fourth industrial revolution [21,48].…”
Section: Introductionmentioning
confidence: 99%
“…The development of manufacturing not only considers technological innovations but also economic, social and environmental effects [4,7]. In the literature, many novel paradigms known as intelligent manufacturing systems (IMS) [8][9][10][11][12][13][14][15] have been proposed such as holonic [16], biological [17], reconfigurable [18], and cloud manufacturing systems [19].In the manufacturing field, Industry 4.0 is characterized by the autonomous systems with cyber and physical representation [20][21][22] and advance in ICT [23] such as cloud computing [24], internet of things (IoT), internet of service (IoS) [25][26][27][28][29], agent technology [30][31][32][33][34][35], cognitive technology [36,37], big data [38,39], data mining [40,41], and artificial intelligence [42][43][44][45][46][47]. Smart manufacturing systems (SMS) built with intelligent cyber-physical systems (CPSs) are the heart of the fourth industrial revolution [21,48].…”
mentioning
confidence: 99%